Java 9 programming for complete beginners in 250 steps - Karanam, Ranga (Packt Publishing, 2019)
"Zero Java Programming Experience? No Problem. Do you want to take the first steps to Become a Great Java Programmer? Do you want to Learn Java Step By Step in a Fail Safe in 28 Minutes Way? Do you want to Learn to Write Great Java Programs? Java is one of the most popular programming languages. Java offers both object-oriented and functional programming features. We take a hands-on approach using a combination of JShell and Eclipse as an IDE to illustrate more than 200 Java Coding Exercises, Puzzles and Code Examples. This course assumes no previous (beginner) programming or Java experience. If you've never programmed a computer before, or if you already have experience with another programming language and want to quickly learn Java, this is a perfect course for you."--Resource description page